Meningkatkan Kualitas Pendidikan Kesehatan Melalui Akreditasi Poltekkes - Saputri, Deasy Eka; Iswan; Ahmad Suryadi Nomi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Accreditation is a strategic effort aimed at enhancing the quality of education at Health Polytechnics (Poltekkes). The accreditation process provides official recognition of the educational standards maintained by the institution, thereby promoting continuous improvement in all academic and non-academic aspects. This study aims to evaluate the impact of accreditation on improving the quality of health education at Poltekkes. The research methodology includes a literature review and secondary data analysis from various relevant sources. The results indicate that accreditation has a positive influence on the quality of education at Poltekkes, particularly in terms of curriculum enhancement, faculty competence, educational facilities, and student satisfaction. There are 76 study programs across 22 Poltekkes, with 36.4% of the programs having excellent accreditation located in Java Island, followed by Poltekkes in Sumatra and Kalimantan. This highlights the need for improving the quality of health education programs in Poltekkes situated in eastern Indonesia (Sulawesi and Papua). The conclusion is that accreditation is an effective tool for improving the quality of health education at Poltekkes, and it needs to be implemented consistently, evenly, and sustainably